Post Pandemic City Rethinking Urban Landscapes through Humanized Management (Global Journal of Human-Social Science, 2025)
The recent epidemiological events and the associated need for scientific knowledge have increased the number of investigations on the impact of diseases in different areas, but at the level of built scenarios, the problems caused by inadequate infrastructure and urban characteristics in coping with health crises are widespread. Given these issues, the general objective of this research is to assess the application of solutions in the field of humanized management of (post-) pandemic urban landscapes, especially in an international context. A scientometric analysis and a systematic review of secondary sources was conducted in the Lens, Scopus, and Web of Science (WoS) databases, quantifying the results and classifying their characteristics to d elineate the main academic discussions. The literature search yielded a total of 200,032 texts, of which 194 were selected for preliminary analysis after applying filters. This showed that publications on WoS (51.35%) and those with empirical approaches (70.62%) predominate, with Europe (33.51%) being more represented, although the United States (12.89%) published a greater number of articles.